2022
DOI: 10.3168/jds.2022-21862
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of a cannabidiol-loaded emulsion stabilized by a whey protein-maltodextrin conjugate and rosmarinic acid complex

Abstract: A cannabidiol (CBD)-loaded oil-in-water emulsion stabilized by a whey protein (WP)-maltodextrin (MD) conjugate and rosmarinic acid (RA) complex was fabricated, and its stability characteristics were investigated under various environmental conditions. The WP-MD conjugates were formed via dry-heating. The interaction between WP and MD was assessed by browning intensity, reduced amount of free amino groups, the formation of high molecular weight components in sodium dodecyl sulfate-PAGE, and changes in secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…Particles of this size exhibited exceptional functional characteristics, including superior stability, prolonged retention in the gastrointestinal tract, increased tissue penetration, and enhanced cellular uptake (Li et al 2021b). WPC had a diameter of approximately 170 nm, which was in line with our previous study (Wang et al 2022a). For soy protein, a significantly larger particle size (180 nm) compared to that of WPC was observed, P < 0.05, which was similar with a previous literature (Baek and Mun 2022).…”
Section: Particle Size Of Blended Wpc and Spi Suspensionssupporting
confidence: 87%
See 2 more Smart Citations
“…Particles of this size exhibited exceptional functional characteristics, including superior stability, prolonged retention in the gastrointestinal tract, increased tissue penetration, and enhanced cellular uptake (Li et al 2021b). WPC had a diameter of approximately 170 nm, which was in line with our previous study (Wang et al 2022a). For soy protein, a significantly larger particle size (180 nm) compared to that of WPC was observed, P < 0.05, which was similar with a previous literature (Baek and Mun 2022).…”
Section: Particle Size Of Blended Wpc and Spi Suspensionssupporting
confidence: 87%
“…WPC had a diameter of approximately 170 nm, which was in line with our previous study (Wang et al . 2022a). For soy protein, a significantly larger particle size (180 nm) compared to that of WPC was observed, P < 0.05, which was similar with a previous literature (Baek and Mun 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is concluded that nanoemulsion of Kencur essential oil with maltodextrin as coating material and tween 80 as a surfactant at this ratio tends to be effective in producing small particle sizes. In contrast to the ratios in other formulas which produce larger particle sizes, namely 110-120 nm [17], 147 nm [18] and 220 nm [19]. Another data we get is the PI value.…”
Section: Effect Of Essential Oil Levels On Particle Sizementioning
confidence: 58%
“…Not only -potential, but also steric hindrance among droplets, is another mechanism to prevent the coagulation or flocculation in emulsions [ 18 ], as it is the main stabilization mechanism [ 54 ], particularly in pickering-type emulsions. Previous studies showed that the union of hydrophilic polysaccharides on the surface of oil droplets reinforces steric repulsion, preventing droplet aggregation [ 55 , 56 ]. The AOE4 shows a -potential close to zero.…”
Section: Resultsmentioning
confidence: 99%